ANALISIS HUBUNGAN ANTARA LABA AKUNTANSI DAN LABA TUNAI DENGAN DIVIDEN KAS - Murtanto; Febby Feiruza Yuridya (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
The objective of the msearch is to examine the relationship between ac-counting income and cash income with cash dividend of consumergood industrylisted in Jakarta Stock Exchange . This adopted correlational method, which determined whether there was relation orcorrelation between accounting income and cashThe variables understudy were accounting income, cash income and cash dividend. The sou4ce of this research data was secondary data, in the form of annual financial statement published by Pusat Referensi Pasar Modal Bursa Efek Jakarta . The analysis used were Spearman's Rank correlation coefficient.The result of the analysis and discussion revealed that there was positive and significant relationship between accounting income with cash dividend and cash income with cash dividend , where the accounting income has greater influence on cash &Mend compared with cash income.Keywords :Accounting income, cash income, cash dividends.